(3TYQ PHjGf ef GdYUQ GdLGgdj Edi fgGjI GdYUQ GdCehj (B/s - (3GdLeGM, Ydj Hf fGUQs ((3CHhXHj (B:s (3gjFI CHhXHj ddSjGMI hGdKbGaI, s (3OGQ GdcJH GdhWfjI,s, 2015)
(3jJfGhd cJGH (B((3TYQ PHjGf ef GdYUQ GdLGgdj Edi fgGjI GdYUQ GdCehj(B) (3hGdPj bGe HLeYg hJMbjbg GdOcJhQ (B((3Ydj Hf fGUQ GdLeGM(B) (3aj MhGdj (B(612) (3UaMI ef GdbWY GdeJhSW GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3eUGOQ TYQ PHjGf hQhGjJg hJhKjbg, GdHGH GdKGfj (B: (3ehVhYGJ TYQ OHjGf, GdHGH GdKGdK (B: (3CZQGV TYQ PHjGf, GdHGH GdQGHY (B: (3GdNUGFU GdafjI, GdHGH GdNGeS (B: (3TYQ PHjGf aj ejRGf GdfbO(B.s
(3HHdjhLQGajI (B: (3UaMI (B585-610.s
Keywords: (3PHjGf (B((3bHjdI(B) (3aj GdTYQ GdYQHjs; (3GdTYQ GdYQHjs -- (3JGQjN hfbOs -- (3GdYUQ GdLGgdjs; (3GdTYQ GdYQHjs -- (3JGQjN hfbOs -- (3GdYUQ GdCehjs